1989
DOI: 10.1159/000217625
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Reactivity of Alpha-Fetoprotein in a Case of Renal Cell Carcinoma

Abstract: The increased serum level of α-fetoprotein (AFP) in a case of renal cell carcinoma, a rare condition of AFP production by mesoderm-derived cells, was evaluated for its lectin reactivity by affinity electrophoresis, followed by the antibody-affinity transfer to nitrocellulose membranes for visualization of separated AFP bands. The AFP of this case was characterized by relative increases of concanavalin A-nonreactive AFP-C1 (60.4%), erythroagglutinating phytohemagglutinin-reactive AFP-P4 (37.8%) and AFP-P5 (46.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…The fucosylation index of AFP (percentage of an LCArcactive fraction in total AFP) was increased (83%) in the present case, while Taketa et al [10] reported the total absence of the LCA-reactive component in a case with renal cell carcinoma. In our previous study [30] fucosyla tion indices of AFP in patients with hepatocellular carci noma (437 cases), carcinoma metastatic to the liver from digestive organs (55 cases), germ cell tumor (10 cases), and nonneoplastic liver diseases mainly representing liver cirrhosis and chronic hepatitis (241 cases) were 39 ± (SD) 31%, 76 ± 27%, 99 ± 2%, and 4 ± 7%, respectively.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…The fucosylation index of AFP (percentage of an LCArcactive fraction in total AFP) was increased (83%) in the present case, while Taketa et al [10] reported the total absence of the LCA-reactive component in a case with renal cell carcinoma. In our previous study [30] fucosyla tion indices of AFP in patients with hepatocellular carci noma (437 cases), carcinoma metastatic to the liver from digestive organs (55 cases), germ cell tumor (10 cases), and nonneoplastic liver diseases mainly representing liver cirrhosis and chronic hepatitis (241 cases) were 39 ± (SD) 31%, 76 ± 27%, 99 ± 2%, and 4 ± 7%, respectively.…”
Section: Discussioncontrasting
confidence: 43%
“…The serum AFP concentration varied from 204 to 24,240 ng/mi in previously reported cases of renal cell car cinoma [5][6][7][8][9][10], In the present case the degree of the incre ment in the AFP concentration was moderate. This study demonstrated four lines of evidence that serum AFP was produced by the renal cell carcinoma: (1) the normaliza tion of the serum AFP concentration was observed after surgery; (2) the tumor tissue concentration of AFP was higher than that of the normal surrounding tissues: (3) the scrum concentration of AFP increased in association with tumor progression, and (4) there was no evidence of other diseases such as hepatocellular carcinoma, chronic liver disease, and germ cell tumor in which AFP could be pro duced.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In any circumstance, when the patient's serum AFP is elevated and the patient does not have explainable liver or germ cell tumors, a search for RCC is recommended because it may be a potential source of serum AFP elevation. Hepatoid RCC is a rare and aggressive variant of RCC [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The following frozen sera, which were obtained from previously described sources [13,20] and had AFP levels from 220 to 650,000 ng/ml (28 of 30 sam ples had AFP levels above 400 ng/ml), were used: cord sera from 3 neonates at full-term delivery and sera from 7 patients with fulminant hepatitis, 10 with chronic liver diseases (6 chronic hepatitis and 4 liver cirrhosis), 11 patients with hepatocellular carcinoma, including a case of mixed hepatocellular/cholangiocellular carcinoma, and 9 other malignant tumors (4 gastric cancer, 1 gallbladder cancer, 1 pancreatic cancer, 1 renal cancer [21], 1 lung cancer [20], and 1 yolk sac tumor). Most of the cases of hepatocellular carcinoma were advanced and all of them had liver cirrhosis as an underlying hepatic lesion.…”
Section: Lectin Preparations and Afp Sourcesmentioning
confidence: 99%